Emotional Intelligence and Burnout Among Otorhinolaryngology–Head and Neck Surgery Residents - Sharaf, Abdulelah M.; Abdulla, Isra H.; Alnatheer, Abdullah M.; Alahmari, Aghadir N.; Alwhibi, Omar A.; Alabduljabbar, Ziyad; Alhamzah, Hamzah; Alkholaiwi, Feras M. (Frontiers in Public Health, 2022)
Background Burnout syndrome is common among surgical residents, negatively affecting their mental health, physical wellbeing, and work performance. We investigated the relationship between emotional intelligence (EI) and burnout among Otorhinolaryngology–Head and Neck surgery residents. Methods This cross-sectional study examined 51 residents across different Otorhinolaryngology-Head and Neck surgery programs at various hospitals in Saudi Arabia using a survey conducted between January 2021 and March 2021. The questionnaire had different validated measurements of burnout and included the Trait EI Questionnaire–Short Form, Maslach Burnout Inventory–Human Services survey, and questions regarding demographics and job satisfaction. Results Of all the residents, 17.6% had a high risk of burnout, 39.2% had emotional exhaustion (EE), 29.4% had depersonalization (DP), and 43.1% had a low sense of personal accomplishment (PA). A statistically significant negative association was observed between the total EI score and EE (r = −0.577, p < 0.001) and DP (r = −0.765, p < 0.001), indicating that higher total EI scores were associated with lower EE levels. Conclusions Positive associations existed between high levels of EI, PA, and satisfaction with both surgical skills and specialty choice. Therefore, residency programs should use EI modifiers as tools to reduce the risk of burnout.